2014
DOI: 10.1002/ijc.29004
|View full text |Cite
|
Sign up to set email alerts
|

Host STAT2/type I interferon axis controls tumor growth

Abstract: The role of STAT2 in mediating the antigrowth effects of type I interferon (IFN) is well-documented in vitro. Yet evidence of IFN-activated STAT2 as having tumor suppressor function in vivo and participation in antitumor immunity is lacking. Here we show in a syngeneic tumor transplantation model that STAT2 reduces tumor growth. Stat2−/− mice formed larger tumors compared to wild type (WT) mice. IFN-β treatment of Stat2−/− mice did not cause tumor regression. Gene expression analysis revealed a small subset of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
22
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 29 publications
(28 citation statements)
references
References 42 publications
2
22
0
Order By: Relevance
“…Studies show that TLR ligands induce DC-mediated cross-presentation in a MyD88-dependent manner (11, 18) but whether other signaling pathways are required for efficient cross-presentation remains unclear. We have recently published that Stat2 −/− cDCs, stimulated with LPS, are defective in tumor antigen cross-presentation in vitro and unable to stimulate anti-tumor Ag specific CD8 + T cells that indeed, upon adoptive transfer in vivo , failed to induce tumor regression (29). In the current study, we now confirm the defect of Stat2 −/− cDCs in cross-priming in vitro with a different Ag (Ovalbumin vs. Pmel-1).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Studies show that TLR ligands induce DC-mediated cross-presentation in a MyD88-dependent manner (11, 18) but whether other signaling pathways are required for efficient cross-presentation remains unclear. We have recently published that Stat2 −/− cDCs, stimulated with LPS, are defective in tumor antigen cross-presentation in vitro and unable to stimulate anti-tumor Ag specific CD8 + T cells that indeed, upon adoptive transfer in vivo , failed to induce tumor regression (29). In the current study, we now confirm the defect of Stat2 −/− cDCs in cross-priming in vitro with a different Ag (Ovalbumin vs. Pmel-1).…”
Section: Discussionmentioning
confidence: 99%
“…A considerable body of literature underscores a prominent role for STAT2 in type I IFN-mediated antiviral (26, 27) and anti-tumor responses (28, 29). STAT2 is ubiquitously expressed in virtually all cell types.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…STAT2 is found to be decreased in many cancers including squamous cell carcinoma of the skin (Clifford et al, 2000;Clifford et al, 2002), fibrosarcoma (Krishnamurthy et al, 2006), astrocytomas (Ehrmann et al, 2008), melanoma (Mischiat et al, 2006), and prostate cancer (Ni et al, 2002). STAT2 has a tumor suppressor function (Clifford et al, 2002;Gamero et al, 2010;Yue et al, 2015) , though the mutations have not yet been identified in human cancer. To evade the antiviral protective effects of IFNs, certain viruses have developed strategies to impair the IFN signaling pathway by specifically targeting STAT2.…”
Section: Implicated Inmentioning
confidence: 99%
“…IFN are endogenous cytokines that have a major role in combatting viral infections. Moreover, there is increasing interest in a role of type I IFN in suppressing tumor growth, notably a role in negatively regulating the cancer stem cell phenotype (8). We and others have previously characterized profound anti-glioblastoma stem cell properties of type I IFN in vitro that involved suppression of sphere formation but relatively little induction of cell death.…”
Section: Introductionmentioning
confidence: 99%